Pelatihan Konsep Administrasi Bisnis sebagai Strategi Pembentukan Karakter Profesional Siswa SMK Negeri 1 Kota Tangerang - Georgius Listen; Andy Andy; Canggih Gumanky Farunik; Agus Kusnawan; Eso Hernawan; Selfiyan Selfiyan; Tri Angreni (BADAN PENERBIT STIEPARI PRESS, 2025)
Professional values in learning activities and work practices. This study aims to analyze the effectiveness of basic business administration concept training as a strategy for building students' professional character at SMK Negeri 1 Tangerang City. The training approach was chosen because of its applicability, contextuality, and ability to instill values such as discipline, responsibility, work ethic, as well as communication and cooperation skills. Through a training design that involves simulations of the world of work, case studies, and real administrative practices, students not only gain conceptual understanding, but also internalize positive work attitudes and behaviors. The results of this study show that practice-based training is effective in increasing students' job readiness, strengthening soft skills, and forming a professional culture in the school environment. These findings recommend the integration of training programs into the curriculum as a strategic effort to produce vocational school graduates who are more adaptive, competitive, and in accordance with the needs of the industrial world. This research contributes to the development of vocational education that emphasizes the synergy between competence and character.